The Enzymatic Antioxidants Activities Changes in Water Plants Tissues Exposed to Chlorpyrifos Stress - Elżbieta Sobiecka; Milena Mroczkowska; Tomasz P. Olejnik (MDPI AG, 2022)
Water pollution is an immense environmental problem, and plant protection products are part of it. The organophosphorus insecticides, chlorpyrifos as an example, were used for years, and their high concentration could negatively influence ecosystems. Some of the plants, such as macrophytes, were exposed to a variety of stress factors. To live on, the macrophytes developed an efficient antioxidative system consisting of enzymatic and non-enzymatic antioxidants. The remediation process of polluted water ecosystems caused by plant protection products in our climate zone can be intensified if it is provided by autochthonic macrophytes. The results of our studies are part of the research that allows optimizing the phytoremediation process without irreversible effect on investigated species. The influence of various concentrations of chlorpyrifos on the enzymatic system in Canadian waterweed (Elodea canadensis Michx.), needle spikerush (Eleocharis acicularis L.), and water mint (Mentha aquatica L.) were studied. The differences in values of guaiacol peroxidase (GPX) and glutathione S-transferase (GST) activities were determined in leaves and roots. Research indicated an increase in both enzyme activities in plants exposed to toxic compounds. The highest concentration of chlorpyrifos affected the highest activities of enzymes. The water mint roots responded with the highest value of glutathione S-transferase activity during cultivation in polluted environment. It was therefore concluded that an aqueous plant exposed to the toxic insecticide created a defensive mechanism by enzymatic antioxidant systems that correlated to the pollutant concentration and plant species.